Everything you need to know about Plan S, Elsevier, and the transition towards Open Science - Aspaas, Per Pippin (2019)
Introduction at seminar for PhD Candidates and Postdocs. Panel debate moderator: Johanne Raade, UiT with contributions from Lene Ottesen, UiT and Kenneth Ruud, UiT. Event organiser: University Library, UiT in collaboration with TODOS (Tromsø Doctoral Students Association). The entire seminar was streamed and can be found on the YouTube channel of TODOS - Tromsø Doctoral Students Association: https://youtu.be/jLH6OqkGHbM.